Microsporum nanum. quarto relato de infecção humana no Brasil - Camargo, Rosangela M. Pires de [UNESP]; Silvares, Maria Regina Cavariani [UNESP]; Carvalho, Cecilia R. B. [UNESP]; Dillon, Neuza Lima [UNESP]; Marques, Silvio Alencar [UNESP] (Instituto de Medicina Tropical, 1992)
Comunica-se o quarto relato de infecção humana por Microsporum nanum (M. nanun) no Brasil. Trata-se de criança de 9 meses de idade, apresentando há um mês lesões cutâneas dorsais compatíveis com tinea corporis. As lesões foram frustas, regredindo espontaneamente após um mês. A investigação epidemiológica na área de origem do caso índice identificou suínos infectados por Microsporum nanum, sugerindo ser esta a fonte de infecção.

The authors present the fourth Brazilian case of human Microsporum nanum (M. nanum) infection. A child of nine months old presents cutaneous dorsal lesions compatible with tinea corporis, which appeared one month before. The culture revealed M. nanum. The lesions resolved spontaneously after a month. Epidemiologic investigation in the patient's place of origin identified swine infected by M. nanum, indicating the probable source of the infection.
Report of the fourth human infection case by Microsporum nanum in Brazil
Keywords: Microsporum nanum; Dermatofitose humana